2013
DOI: 10.7314/apjcp.2013.14.11.6399
|View full text |Cite
|
Sign up to set email alerts
|

Association of an LMP2 Polymorphism with Acute Myeloid Leukemia and Multiple Myeloma

Abstract: Hematological malignancies (HM) are a group of neoplasms derived from the cells of the bone marrow and lymphatic system. Genetic factors leading to susceptibility to HM have been investigated for years but little is known yet. Low molecular weight polypeptide (LMP) 2 and LMP7 genes are important subunits of the immunoproteasome and play significant role in antigen presentation. The polymorphisms of LMP genes have been reported to be risk factors for various types of diseases. The aim of this study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…These results were consistent with those reported in the majority of previous studies that investigated the association between polymorphisms in LMP2 and LMP7, and other diseases (11-13,22,23). However, Ozbas-Gerceker et al reported that LMP2 plays a role in the development of acute myeloid leukemia and multiple myeloma, whereas LMP7 is not a risk factor for hematological malignancies (24). The discrepancy between these results and the present findings may be attributed to the fact that the same polymorphism may exert different genetic effects on various types of cancer (25,26).…”
Section: Discussioncontrasting
confidence: 56%
“…These results were consistent with those reported in the majority of previous studies that investigated the association between polymorphisms in LMP2 and LMP7, and other diseases (11-13,22,23). However, Ozbas-Gerceker et al reported that LMP2 plays a role in the development of acute myeloid leukemia and multiple myeloma, whereas LMP7 is not a risk factor for hematological malignancies (24). The discrepancy between these results and the present findings may be attributed to the fact that the same polymorphism may exert different genetic effects on various types of cancer (25,26).…”
Section: Discussioncontrasting
confidence: 56%
“…Hematologic malignancies are a common disease in Asian Pacific areas (Feng et al, 2013;Jiang et al, 2013;Karami et al, 2013;Khodabandehloo et al, 2013;Kooshyar et al, 2013;Li et al, 2013;Liu et al, 2013;Ozbas-Gerceker et al, 2013;Qin et al, 2013;Shan et al, 2013). As our present study confirmed, the level of serum ferritin of patients with hematologic malignancies was significantly increased.…”
Section: Discussionsupporting
confidence: 78%
“…The eligible studies presented data for several different cancer types, including gastric cancer, cervical cancer, ovarian cancer, hematological malignancy, colorectal cancer and esophageal squamous cell carcinoma. Among these 19 studies, 11 were based on Asian populations [ 7 - 9 , 14 - 16 ], 8 on Caucasian populations [ 10 - 13 ]. Furthermore, the genotyping methods utilized in the studies included PCR-RFLP (RFLP, restriction fragment length polymorphism), Taqman, Sequencing and ARMS-PCR (ARMS, amplification refractory mutation system).…”
Section: Resultsmentioning
confidence: 99%